CLASS B0445+123: a new two-image gravitational lens system - Argo, Megan; Jackson, N.; Browne, I.; York, T.; McKean, J.; Biggs, A.; Blandford, R.; deBruyn, A.; Chae, K.; Fassnacht, C.; Koopmans, L.; Myers, S.; et al. (Wiley-Blackwell Publishing Ltd., 2003)
A new two-image gravitational lens system has been discovered as a result of the Cosmic Lens All-Sky Survey. Radio observations with the Very Large Array (VLA), the Multi Element Radio Linked Interferometer Network and the Very Long Baseline Array at increasingly higher resolutions all show two components with a flux density ratio of ~7 : 1 and a separation of 1.34 arcsec. Both components are compact and have the same spectral index. Follow-up observations made with the VLA at 8.4 GHz show evidence of a feature to the south-east of the brighter component and a corresponding extension of the weaker component to the northwest. Optical observations with the William Herschel Telescope show ~1.7-arcsec extended emission aligned in approximately the same direction as the separation between the radio components with an R-band magnitude of 21.8 ± 0.4.